The Talented Mr. Golden Visa: Indonesia Temporary Tax Resident - Hapsari, Nidya (Inovbiz: Jurnal Inovasi Bisnis, 2024)
This study builds on a growing body of research on the territorial taxation of foreign talents with specific skills or expertise by analyzing the compatibility with the immigration policy in Indonesia. It is claimed that both the Golden Visa and Temporary Tax Resident policies will attract skilled foreign workers and foreign investments in Indonesia. However, irrespective of the increase of foreign professional roles over the last 2 (two) years, the study found that combining both policies is yet to be optimum to increase the ease of doing business in Indonesia. This study employs a qualitative approach by examining relevant laws, regulations, published literature, and media articles; and running comparative studies with temporary resident policies in Australia, Japan, and Singapore. In finding the semi-worldwide Income Tax system as relevant to Indonesia and some recommendations to establish harmony between the immigration and tax policies, the study contributes to developing more consistent and competitive residency policies in Indonesia.